Anatomy of point-contact Andreev reflection spectroscopy from the experimental point of view (Review Article): - Naidyuk, Yu.G.; Gloos, K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
We review applications of point-contact Andreev-reflection spectroscopy to study elemental superconductors, where theoretical conditions for the smallness of the point-contact size with respect to the characteristic lengths in the superconductor can be satisfied. We discuss existing theoretical models and identify new issues that have to be solved, especially when applying this method to investigate more complex superconductors. We will also demonstrate that some aspects of point-contact Andreev-reflection spectroscopy still need to be addressed even when investigating ordinary metals.